The Effect Of Reciprocal Teaching On Reading Comprehension To The Eleventh Year Students Of Sma I Pallangga Gowa In Academic Year 2013/2014 - Sumarni . (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
This research was conducted to know the effect of using  Reciprocal Teaching Strategy to improve the students’ reading comprehension and also to know what type of reading comprehension are dominantly affected by using Reciprocal Teaching. The research applied Quasi-Experimental design. This research was designed into two groups; Experimental group and Control group. Each group consisted of 36 students. The sample was chosen by using simple random technique which used lottery technique. The data were collected through multiple choice reading test both in experimental group and control group namely pretest and posttest. The data collected through reading test were analyzed by using SPSS 20.0 version.The research findings showed that the mean score and standard deviation for each group, getting fair classification on their posttest result,  means that both experimental which uses Reciprocal Teaching Strategy and control group which uses Direct Teaching method in measuring students’ reading ability have same improvement or there was no difference significantly between both of them(t observe= 1.729< t table = 1.999 and p=0.08 > 0.05). Besides, all three levels of comprehension improved. It was proven by comparison of mean score of pretest and posttest on all level of both groups. The difference of pretest and posttest mean score both of groups was statistically significant to inferential and critical level (p=0.03). Although, this research have a little bit of improvement in experimental group but the result still be believed that using reciprocal teaching affect dominantly in improving inferential and critical comprehension. It means that this strategy can support reader to get the comprehensible one of different genre of reading text.